XIAP (X-linked Inhibitor of Apoptosis) gene therapy protects photoreceptors in an animal model of retinal detachment-induced apoptosis - Zadro-Lamoureux, Laura (University of Ottawa (Canada), 2009)
Retinal detachments cause photoreceptor apoptosis. XIAP (X-linked inhibitor of apoptosis) inhibits caspases-3, -7, and -9, which prevents the apoptotic cascade. This study evaluates XIAP gene therapy as a means to provide photoreceptor neuroprotection following retinal detachment. Subretinal injections of virally-delivered XIAP or green fluorescent protein (GFP; injection control) were performed in rats. Two weeks later, retinal detachments were created at the viral injection site. Eyes were harvested 24 hours post-detachment to analyze caspase activity and at 3 days and 2 months for histological analysis. Caspase assays indicated rises in caspase-3 and -9 activities in detached GFP-treated retinas, whereas XIAP-treated retinas behaved comparably to attached controls. Three day TUNEL analysis showed less apoptosis in XIAP-treated detachments. Two month histology confirmed preservation of photoreceptors in XIAP-treated detachments, whereas GFP-treated detached retinas had deteriorated significantly. The results suggest that XIAP confers structural photoreceptor neuroprotection for at least two months following retinal detachment.
Keywords: Biology, Molecular.